TOC and CaCO3 content in Oligocene shelf deposits on Lemnos Island and their relation with depositional conditions - Nioti, D.; Maravelis, A.; Tserolas, P.; Zelilidis, A. (Bulletin of the Geological Society of Greece, 2013)
A series of seventy seven samples from outcrops of mudstones were analyzed in order to evaluate their total organic carbon (TOC) and calcium carbonate (CaCO3) concentrations. Results showed that TOC ranges between 0% to 1.15% (with a mean value of 0.34%) introducing that Oligocene shelf deposits on Lemnos island have fair to good conditions to be potential source rocks. Analysis of CaCO3 presented a range between 1.37% to 42.52% (with a mean value of 16.95%). The comparison of TOC and CaCO3 suggests that the two parameters are either inversely or positively related. The inversely related contents, high TOC and low CaCO3, may indicate anoxic conditions, whereas low TOC and high CaCO3 occur in oxic conditions due to the decomposition of TOC. The CO2 produced by decomposition of organic carbon and production of organic acids reduces the pH in pore water enough to dissolve any CaCO3 that reaches the sediment water interface. On the other hand, a positive relation, with both high TOC-CaCO3 contents, could be related with oxic conditions and high sedimentation rate or incidents of abrupt death and bury of great amounts of benthic organisms (TOC) increasing the maintenance of organic material in the sediment.